Dupilumab-associated sezary syndrome - Austin Hamp; Jamie Hanson; Albert Alhatem; Robert A Schwartz (Indian Journal of Dermatology, 2023)
Dupilumab is a monoclonal antibody that inhibits interleukin-4 (IL-4) and interleukin-13 (IL-13), approved for the treatment of adults with moderate-to-severe atopic dermatitis (AD). While recent reports have described cases of new-onset mycosis fungoides (MF) following treatment with dupilumab for AD, to our knowledge only one patient has been delineated with the progression to SS. We present an additional case of a patient who was diagnosed with SS following treatment with dupilumab for adult-onset AD and asthma. We examine SS as a possible side effect of dupilumab while also discussing management and theories to explain this phenomenon.